LUMPY SKIN DISEASE VIRUS: APPROACHES TO ATTENUATION FOR VACCINE DEVELOPMENT - Chervyakova , O.V.; Sultankulova , K.T.; Nissanova , R.K.; Orynbayev , M.B. (Eurasian Journal of Applied Biotechnology, 2019)
Lumpy skin disease (LSD) is a disease caused by the lumpy skin disease virus (LSDV) of the genus capripoxvirus. The disease is responsible for serious losses to the cattle industry globally. Vaccination is the most effective way of controlling LSDV. The currently available live attenuated vaccines are used in many countries and provide stable immunity. However, use of these vaccines can sometimes cause postvaccinal complications in animals. Attenuation of viruses by the classical method is associated with random mutations in the genome, and some vaccines can contain a mixture of viruses of different genotypes and virulence. Hence, there is a need to develop a safe immunogenic vaccine that will provide improved protection against LSDV. The most promising approach is gene modification to develop an attenuated capripoxvirus strain with high immunogenicity and protectivity. Sequencing and analysis of capripoxvirus DNA genomes has resulted in the identification of a number of genes whose protein products effectively stimulate antibody production in the host organism. These proteins are able to function both inside and outside the cell, neutralizing the complement factors, inhibiting apoptosis and synthesis of interferons, and reducing counter-inflammatory cytokines and chemokines. Here, we review the literature for instances of genetic manipulation of genes encoding the above proteins, resulting in capripoxvirus attenuation.